2022
DOI: 10.1155/2022/3926977
|View full text |Cite
|
Sign up to set email alerts
|

Blame the Message Senders Not the Messenger: The Defence Case of the English “Native Speaker” Teacher

Abstract: This article investigates how “native speaker” teachers define who a “native speaker” is and how they view themselves in relation to the concept. It further explores how they feel about discriminatory practices in employability and the pay gap that are systemically carried out against their “nonnative speaker” counterparts by recruiters. Data were gathered from 10 English language teachers: five males and five females from the UK, Canada, Ireland, and South Africa, who were hired by a state university in Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Wang and Fang (2021) have reported that stakeholders do not perceive a substantial distinction between the two groups of English instructors, despite the deeply rooted native-speakerism in the field of English Language Teaching (ELT) that favors Native English-Speaking Teachers (NESTs) as the ideal English educators while Non-Native English-Speaking Teachers (NNESTs) are often marginalized. Alqahtani (2022) conducted a study that examined the criteria used for hiring "native speakers" in relation to their place of birth and the official status of English in a given country. The study found that while these criteria were considered the main defining factors by recruiters, non-native English-speaking teachers (NESTs) did not share the same perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Fang (2021) have reported that stakeholders do not perceive a substantial distinction between the two groups of English instructors, despite the deeply rooted native-speakerism in the field of English Language Teaching (ELT) that favors Native English-Speaking Teachers (NESTs) as the ideal English educators while Non-Native English-Speaking Teachers (NNESTs) are often marginalized. Alqahtani (2022) conducted a study that examined the criteria used for hiring "native speakers" in relation to their place of birth and the official status of English in a given country. The study found that while these criteria were considered the main defining factors by recruiters, non-native English-speaking teachers (NESTs) did not share the same perspective.…”
Section: Introductionmentioning
confidence: 99%